Cutaneous tuberculosis with nonreactive PPD skin test: a diagnostic challenge - Priscila Wolf Nassif; Ana Paula Zanatta Rosa; Ana Cristina Medeiros Gurgel; Paula Aline Zanetti Campanerut; José Fillus Neto; Rosilene Fressatti Cardoso (Sociedade Brasileira de Dermatologia, 2015)
The authors report a case of cutaneous tuberculosis in a 63-year-old female patient, who had an infiltrated, erythematous-ferruginous plaque of indurated aspect on her right leg and a nonreactive PPD skin test. Diagnosis was made by tissue culture and PCR of skin biopsy material. The treatment was performed with pyrazinamide, rifampicin, isoniazid and ethambutol, with good response.